2017
DOI: 10.13189/ujes.2017.050102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Card Yarn Properties Produced from Conventional Ring and Compact Spinning

Abstract: Yarn characteristics extensively influence by spinning process. The aim of this study is to observe the effect of conventional ring and compact spinning processes on properties of yarn. 100% CIS-Turkey cotton was used to produce conventional ring card yarn and card compact yarn. The twist per inch of 16.99 and 19.57 were settled to fabricate 20 Ne and 30 Ne count of yarn respectively both for conventional ring and compact spinning. The positive effect of spinning process on the yarn properties were evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Many researchers have already studied the effect of waste on yarn quality from different perspectives. The results of several investigations have revealed that the waste of different sections of the apparel industry significantly affects the physical and mechanical properties of the yarn [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Jamshaid et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have already studied the effect of waste on yarn quality from different perspectives. The results of several investigations have revealed that the waste of different sections of the apparel industry significantly affects the physical and mechanical properties of the yarn [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Jamshaid et al.…”
Section: Introductionmentioning
confidence: 99%